PERSFEKTIF EKONOMI DAN SOSIAL KONSUMEN TERHADAP DAYA BELI BERAS MERAH DAN BERAS PUTIH DI PASAR BAYONGBONG KABUPATEN GARUT - Nugraha, Ade; Sudirman; Septian, Yugi Sadrah; Murwenie, Ira (Jurnal Ekonomi Manajemen Bisnis Dan Akuntansi : EMBA, 2024)
The purpose of this study was to compare the purchasing power of brown rice and white rice in Bayongbong market, Garut Regency. Based on the economic and social perspectives of consumers. It can be seen that the consumption of brown rice shows an increasing trend, along with public awareness of the importance of a healthy diet. This study uses a quantitative approach to determine how much consumer purchasing power is based on the economic and social perspectives of consumers towards the two types of rice, with a focus on economic aspects (price and purchasing power) and social (health awareness). The results of the study showed that the price of brown rice can influence consumer purchasing power by 88.0% (R ^ 2) and white rice by 83.0% (R ^ 2). This means that consumer decisions in purchasing brown rice and white rice are influenced by price fluctuations but are based on the economic and social perspectives of consumers.